Adaptive responses to high salinity of two subspecies of Aster tripolium on different nitrogen sources - Sági, Bernadett; Erdei, László (Acta Biologica Szegediensis, 2005)
The effects of NaCl salinity, different N-sources (nitrate or ammonium), as well as pH on the major enzymes of N-metabolism and total antioxidant capacity were investigated in two subspecies of Aster tripolium L., A. tripolium ssp. tripolium, a maritime halophyte, and A. tripolium ssp. pannonicus, endemic on the continental alkaline salty meadows. Differences in their biochemical and physiological responses to the experimental conditions are in agreement with their evolutional adaptation either to the fluctuating coastal circumstances or to the more constant salinity level on the alkaline salty meadows. Accordingly, A. tripolium ssp. tripolium reacted more sensitively to salinity while A. tripolium ssp. pannonicus showed less physiological flexibility and more stable performance.